An updated subjective global checklist of the extant non-marine Ostracoda (Crustacea) - Claude Meisch; Robin J. Smith; Koen Martens (European Journal of Taxonomy)
We present an updated global checklist of extant non-marine Ostracoda, covering taxonomic changes in the published literature up to 31st December 2023. The checklist is subjective, as apart from published taxonomic changes, also some additional alterations are proposed, including ten candonid tribes which are upgraded to subfamilies, six new combinations, one new name, five synonymies and one new taxonomic placement. The checklist presently includes 2420 accepted species in 295 genera, as well as 84 uncertain species that are too poorly described to be recognisable. We also provide the totals of species numbers for each taxonomic rank, from genera up to order, and numbers of species and endemic species in each of the world’s major zoogeographical regions.